Q: Factor 3ab plus a plus 3b squared plus b?

Write your answer...

Submit

Related questions

6

(3b - 1)(a - b)

(3b - 1)(a - b)

3ab - a - 3b2 + b = -3b2 + 3ab + b - a = -3b(b - a) + 1(b - a) = (1 - 3b)(b - a)

(2a + b)(a + 3b)

Divide by 6a: 6a(a + 3b)

No

-1

(3b + 7x)(3b + 7x) or (3b + 7x)2

(3b - 4)(3b - 4)

3b2 - 3b = 3b(b - 1)

(b - 1)(3b - 10)

(a + 3)( b + 2)

(x + 3)(a + b)

3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)

3(4a+b+2c)

This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)

(3b + 4x)(2q + v)

a(b+3)+b(b+3)

2b - 1

Since 3b is a factor of 9b, it is automatically the GCF.

12ab + 13b + 4 (assuming there's addition in the spaces)

You would factor 3a + 9b as: 3(a+3b)

5 + 10ac + 3b

3b

People also asked

Study guides